#TITLE_ALTERNATIVE# - Samudra Nugraha (NIM 151 03 055), Sanny
Abstract : Massive earthquake followed by tsunami in Aceh may result quite big co-seismic deformation value. Aceh and its surroundings areas has been predicted to have more than 2 meters of land shifting. There will be problems of geometrical spatial data in Aceh due to this massive deformation. One example of the problem is the geometrical status of boundaries whether it is a state or region boundaries. With the data from GPS field measurement after the earthquake at Acehs segment, the model of co-seismic deformation is made with elastic half space. From that model the deformation of points at boundaries can be determined whether state or region boundaries at Acehs segment. The shifting of boundaries point at Aceh due to the co-seismic deformation gave a various effects. From 9.45 cm at province boundary in the west coast of the Aceh-North Sumatra boundaries, until the highest one 260.3 cm between west Aceh Kabupaten and Aceh Besar in the west coast near the epicentrum of the quake. Co-seismic deformation of the Aceh earthquake has a direction angle an shifting at 241 degree until 275 degree or mean angle at southwest. By knowing the shifting of boundaries points at state or region which over the limit of accuration on land (for PBU and PABU (Pilar Acuan Batas Utama) = +/- 15 cm and for PBA and PABA (Pilar Acuan Batas Antara) = +/- 25 cm) also the limit of accuration off shore +/- 1.5 m. So the geometry of deformated boundaries points has become in appropriate with legal aspects or technical aspects that shuold have been fulfilled by the boundaries points, so it must some things to do with this boundaries points geometry problem.